PcASTA in Procambarus clarkii, a novel astaxanthin gene affecting shell color - Chen, Xiajun; Chen, Jing; Huang, Long; Wu, Benli; Wu, Cangcang; He, Jixiang; Bai, Zhiyi (Frontiers in Marine Science, 2024)
The color of crayfish (Procambarus clarkii) shells not only affects their value, but also has a significant impact on individual size. Astaxanthin is a common carotenoid that has been found in many studies to have different functions, including regulating body color formation. In this study, the levels of different carotenoids were detected using high performance liquid chromatography (HPLC) and found a significant correlation between astaxanthin content and shell color. An astaxanthin gene (PcASTA) was identified from P. clarkii, and it was expressed in tissues of crayfish with dark-red shells and green shells. The highest expression levels of PcASTA were found in the hepatopancreas, followed by the muscle. The expression of PcASTA in all tissues of red shell crayfish was higher than that of green shell crayfish, indicating that PcASTA may be involved in shell color formation in crayfish. Moreover, high water temperature and feeding β-carotene can lead to an increase in tissue expression of PcASTA and astaxanthin content in crayfish shells. The findings indicate that PcASTA may affect shell color in P. clarkii by being involved in astaxanthin synthesis and transformation.